Close interactions between the Antarctic cyclone budget and large‐scale atmospheric circulation. Issue 12 (21st June 2013) - Uotila, Petteri; Vihma, Timo; Tsukernik, Maria
Abstract: [1] For the first time, we quantify relationships between the Southern Ocean cyclones and large‐scale atmospheric variability indices: the Southern Annular Mode (SAM), the El Niño–Southern Oscillation (ENSO), the Zonal Wave 3 (ZW3) pattern, and the semiannual oscillation (SAO). Using the ERA‐Interim 1979–2011 results, we identify cyclones south of 40°S and calculate monthly sectoral cyclone budgets of the Southern Ocean, defined as cyclogenesis minus cyclolysis plus net movement of cyclones into each sector. The SAM index has a strong connection with cyclones across all sectors. Positive SAM values are related to decreased eastward and increased southward movement of cyclones, resulting in higher cyclone densities along the Antarctic coast. The ENSO index shows strong associations with the cyclone behavior in the Amundsen‐Ross Seas, whereas other regions are less sensitive to it. The ZW3 index has a stronger association with the meridional movement of cyclones than other indices. Key Points: SAM values are related to movement of cyclones Meridional movement of cyclones mostly associated with ZW3 Impact of ENSO in the Amundsen‐Ross Seas is comparable to that of SAM